2019
DOI: 10.1186/s12967-019-02146-5
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the inflammatory response during BBN-induced bladder carcinogenesis in mice

Abstract: BackgroundBladder cancer (BC) is the most common malignant disease of the urinary tract. Recurrent high grade non muscle invasive BC carries a serious risk for progression and subsequent metastases. The most common preclinical mouse model for bladder cancer relies on administration of N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN) to mice. BBN-induced tumors in mice recapitulate the histology of human BC and were characterized with an overexpression of markers typical for basal-like cancer subtype in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Among pre-clinical models used to study urothelial cancer, are wild type animals exposed to OH-BBN [N-butyl-N-(4-hydroxybutyl) nitrosamine] [17], genetically engineered murine (GEM) models [18] or allografted tumorigenic cell lines such as MB49 (DMBA-in vitro transformed urothelial cells) [19] and MBT-2 (FANFT-induced bladder tumor in C3H/He mouse) [20]. The subtype and grade of OH-BBN induced tumors depend on genetic background, strain and sex [16,21]. In wild type C57BL/6 mice, prolonged exposure to OH-BBN (20 weeks) is required to induce MIBC that represents the molecular subtypes and mutational landscape found in humans [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among pre-clinical models used to study urothelial cancer, are wild type animals exposed to OH-BBN [N-butyl-N-(4-hydroxybutyl) nitrosamine] [17], genetically engineered murine (GEM) models [18] or allografted tumorigenic cell lines such as MB49 (DMBA-in vitro transformed urothelial cells) [19] and MBT-2 (FANFT-induced bladder tumor in C3H/He mouse) [20]. The subtype and grade of OH-BBN induced tumors depend on genetic background, strain and sex [16,21]. In wild type C57BL/6 mice, prolonged exposure to OH-BBN (20 weeks) is required to induce MIBC that represents the molecular subtypes and mutational landscape found in humans [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In wild type C57BL/6 mice, prolonged exposure to OH-BBN (20 weeks) is required to induce MIBC that represents the molecular subtypes and mutational landscape found in humans [22][23][24]. However, commonly only male mice of the C57BL/6 strain are used in such studies, disregarding the sex-biased disease outcome and response to therapy [16,21,22]. On the other hand, most GEM models acquire urothelial hyperplasia and papillary non-progressive NMIBC instead of MIBC [25], and do not reflect the heterogeneous mutational landscape and gene expression profile of human tumors [16,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, Degoricija et al, showed the immunologic alterations and higher expression of immune checkpoint molecules in tumors from young male mice at 20 weeks following exposure to BBN carcinogen. 31 Although this is one of the few reports that have characterized some local inflammatory changes accompanying carcinogens, this study was conducted in young male mice. Based on our observation on increased PD-L1 protein expression in the urothelial and endothelial cells, it can be speculated that this may result from BBN induced DNA damage and activation of cellular IFN pathways.…”
Section: Discussionmentioning
confidence: 99%
“…BBN is a nitrosamine that is metabolized in the liver to N-butyl-N-(3-carboxypropyl)nitrosamine (BCPN), which is found in tobacco products (Bonfanti et al, 1988;Cohen, 1998;Mirvish, 1995). Five months of exposure to BBN induces basal subtype tumors, however short exposure induces a potent inflammatory response that resolves by about one month and recedes as tumors form (Degoricija et al, 2019).…”
Section: Short Term Treatment With Carcinogens Primes K14-basal Cells For Tumor Formation Bymentioning
confidence: 99%